BLENDED LEARNING: IMPLICATIONS FOR GROWTH AND ACCESS - Anthony G. Picciano (Online Learning, 2019)
The purpose of this paper is to reflect on issues of growth and access in blended learning environments. Increasingly decision makers throughout higher education are considering blended learning as an important component of their academic programs. It is hoped that this paper will help to provide insight for these decision makers. Many of the thoughts and ideas in this paper evolved out of discussions on Growth Paradigms held at the 2005 Sloan-C Summer Workshop in Victoria, British Columbia, and the 2004 and 2005 Sloan-C Workshops on Blended Learning held in Chicago.